ULTIVATING STUDENT’S INTERPRETING SKILLS (International journal of artificial intelligence, 2024)
This article explores effective techniques that should be designed to cultivate students’ interpreting skills; split-attention/dual-task exercises can be helpful to develop concentration and a powerful memory, as the interpreter/translator must have a powerful memory; he/she should train it consistently through and in practice. The author discusses all the skills and techniques required for a good interpreter, particularly memory, which is the first one that should be introduced to trainee interpreters.